Immunogenicity of pembrolizumab in patients with advanced tumors. Issue 1 (8th August 2019) - van Vugt, Marianne J. H.; Stone, Julie A.; De Greef, "Rik" H. J. M. M.; Snyder, Ellen S.; Lipka, Leslie; Turner, David C.; Chain, Anne; Lala, Mallika; Li, Mengyao; Robey, Seth H.; Kondic, Anna G.; De Alwis, Dinesh; et al.
Abstract : Background: Pembrolizumab is a potent, humanized, monoclonal anti–programmed death 1 antibody that has demonstrated effective antitumor activity and acceptable safety in multiple tumor types. Therapeutic biologics can result in the development of antidrug antibodies (ADAs), which may alter drug clearance and neutralize target binding, potentially reducing drug efficacy; such immunogenicity may also result in infusion reactions, anaphylaxis, and immune complex disorders. Pembrolizumab immunogenicity and its impact on exposure, safety, and efficacy was assessed in this study. Patients and methods: Pembrolizumab immunogenicity was assessed in 3655 patients with advanced or metastatic cancer treated in 12 clinical studies. Patients with melanoma, non–small cell lung cancer, head and neck squamous cell carcinoma, colorectal cancer, urothelial cancer, and Hodgkin lymphoma were treated with pembrolizumab at 2 mg/kg every 3 weeks, 10 mg/kg every 2 weeks, 10 mg/kg every 3 weeks, or 200 mg every 3 weeks. An additional study involving 496 patients with stage III melanoma treated with 200 mg adjuvant pembrolizumab every 3 weeks after complete resection was analyzed separately. Results: Of 3655 patients, 2000 were evaluable for immunogenicity analysis, 36 (1.8%) were treatment-emergent (TE) ADA-positive; 9 (0.5%) of these TE-positive patients had antibodies with neutralizing capacity. The presence of pembrolizumab-specific ADAs did not impact pembrolizumab exposure, nor did pembrolizumab immunogenicity affect the incidence of drug-related adverse events (AEs) or infusion-related reactions. There was no clear relationship between the presence of pembrolizumab-specific ADAs and changes in tumor size across treatment regimens. Of the 496 patients treated with pembrolizumab as adjuvant therapy, 495 were evaluable, 17 (3.4%) were TE ADA–positive; none had neutralizing antibodies. Conclusions: The incidence of TE (neutralizing positive) ADAs against pembrolizumab was low in patients with advanced tumors. Furthermore, immunogenicity did not appear to have any clinically relevant effects on the exposure, safety, or efficacy of pembrolizumab. Trial registration: ClinicalTrials.gov, NCT01295827 (February 15, 2011), NCT01704287 (October 11, 2012), NCT01866319 (May 31, 2013), NCT01905657 (July 23, 2013), NCT02142738 (May 20, 2014), NCT01848834 (May 8, 2013), NCT02255097 (October 2, 2014), NCT02460198 (June 2, 2015), NCT01953692 (October 1, 2013), NCT02453594 (May 25, 2015), NCT02256436 (October 3, 2014), NCT02335424 (January 9, 2015), NCT02362594 (February 13, 2015).